(Use of Totally Physical Response Learning Model (TPR) to Increase English Learning Results on Discussion Learning Text for Class XII IPS 2 Students SMA Negeri 1 Salo) - Arianti, Novita (UIR Press, 2018)
Classroom action research has been conducted in SMA Negeri 1 Salo on subjects in English with a class XII student research object IPS second at odd semester 2015/2016. This research was done in an effort to improve the learning outcomes of English on the subject of Discussion Text for students of class XII IPS2.learning model TotallyPhysical Response (TPR) have to be applied after through observation and reflection carried out by the researcher. Researchers plan of action based on the results of observation and reflection that has been done through the development of learning-based learning tools Totally Physical Response (TPR), which consists of test questions (repeat), observation sheets and lesson plans and other supporting learning device.learning model TotallyPhysical Response (TPR) in accordance with the Education Unit Level Curriculum (SBC) consists of four main stages, namely: students to engage in dialogue, role playing, presentation materials, as well as reading and writing. This study can be completed in 2 cycles of 4 meetings and four times daily tests. Results of research is observational data and the recapitulation of the test (replications) and recapitulation completeness study shows there has been increased activity of a positive student learning in the classroom and an increase in the mean test (replications) and increasing the classical completeness of cycle 1 to cycle 2. Activity of students during the process learning is observed by the observer as the data for evaluation and reflection. Recapitulation mean test (replications) and mastery learning test scores obtained from Cycle 1 and repeat the cycle 2. Based on the results of this study concluded that the application of the learning model Totally Physical Response (TPR) in class XII IPS 2 SMA Negeri 1 Salo able to improve learning outcomes of subjects in English as indicated by the mean of the test (replications) and classical completeness in every cycle.